Perspectives of maintaining community-based animal health services in the highlands of eastern Hararge: Implications of operating under unclear policy environments - Ayalew, W.; Rischkowsky, Barbara A. (2004)
Implementation of Community-based Animal Health Service (CARS) in Eastern Hararghe Zone, of the Oromia Regional State was an important component of the Dairy Goat Development Programme (DGDP). DGDP had been implemented between 1989 and 1997 in selected areas of Ethiopian highlands to improve household welfare through better feeding, health care and breeding of goats. This paper tests the hypothesis that local institutions would continue to provide technical supervision to the community-based animal health workers (CAHWs) after cessation of support from the DGDDetailed comparative data was generated on CAHWs activity between July 1998 and June 1999 from Gursum and Kombolcha districts of Eastern Hararghe. The results showed that despite: the continued demand in the communities for the service of CAHWs, their activities had been declining mainly due to lack of a system of drug; supply, technical supervision and refreshment training; which should have been provided from the government veterinary offices. It was concluded that although the idea of bringing; basic veterinary services closer to the villages was upheld at all levels, delivering; the service had become difficult. This was explained by the vague policy environment on the operation of CAHWs and on how these should be integrated into the network of government veterinary services. The unclear central level policy positions were open for inconsistent local interpretations. The debate on the merit and demerit of CAHWs is misleading as it often ignores the complementary relationship between the CAHWs and government veterinary services. The success of CAHS, therefore, depends partly on clear policy guidelines on the provision of adequate technical veterinary consultation as well as on direct participation of local and national veterinary authorities in their implementation. As CAHS is ideally built upon extensive community participation, the services are likely to be responsive to local needs and problems.